The effect of using Navigation style in educational blogging on academic achievement for English Language curriculum to the second- grade students in Prince Abdul Majeed secondary school in Medina - Al- Ahmadi, Sami Muhammad (Journal of Educational and Psychological Sciences, 2020)
The objective of this research to find out the effect of using Navigation style in educational blogging on academic achievement for English Language curriculum (the present perfect and the present perfect continuous) to the second- grade students in secondary Medina. The search was based on the quasi-experimental approach, where research has been applied to a sample of the 30 students from the second grade students were selected from secondary school secondary Prince Abdul Majeed Medina, in the second semester of the academic year 1433- 1434 AH. The students were divided into two groups of them (15) as an experimental group studied English grammar through Menu Navigation style. And (15) students studied the same rules by Hierarchical Navigation. The search tool was an achievement test and make sure of its sincerity and firmness before actually applied on the two sets of search. And reached results that there is no statistically significant differences at the level (0.05) between the average student achievement in the experimental group- who has studied the rules of English through Hierarchical Navigation style- and the average student achievement in the group Experimental II- who has studied the rules of the English language on Menu Navigation style- in the post- test for the experimental group. The following recommendations can be made after the previous results as use electronic blogs to teach the English language in general and to teach its grammar in particular, as its use as a modern educational method contributes to raising the level of academic achievement of students compared to traditional educational methods in teaching the English language and its rules. Also, Urging the teachers of the English language to use the electronic blog as an educational method in their teaching of the English language subject and its rules by making them aware of the active role in the classroom, as it contributes to raising the level of student performance in learning the English grammar. Finally, Encouraging researchers to conduct more scientific studies that explain the feasibility of using electronic blogs as an educational method in teaching the English language and its rules in stages and educational classes other than the ones covered in this study.
Keywords: Navigation style; educational blogging; academic achievement; the second grade